Vicariance Between Cercis siliquastrum L. and Ceratonia siliqua L. Unveiled by the Physical–Chemical Properties of the Leaves’ Epicuticular Waxes - Pereira, Rui F. P.; Rocha, João; Nunes, Paulo; Fernandes, Tânia; Ravishankar, Ajith P.; Cruz, Rebeca; Fernandes, Mariana; Anand, Srinivasan; Casal, Susana; de Zea Bermudez, Verónica; Crespí, António L. (Frontiers in Plant Science, 2022)
Classically, vicariant phenomena have been essentially identified on the basis of biogeographical and ecological data. Here, we report unequivocal evidences that demonstrate that a physical–chemical characterization of the epicuticular waxes of the surface of plant leaves represents a very powerful strategy to get rich insight into vicariant events. We found vicariant similarity between Cercis siliquastrum L. (family Fabaceae, subfamily Cercidoideae) and Ceratonia siliqua L. (family Fabaceae, subfamily Caesalpinoideae). Both taxa converge in the Mediterranean basin (C. siliquastrum on the north and C. siliqua across the south), in similar habitats (sclerophyll communities of maquis) and climatic profiles. These species are the current representation of their subfamilies in the Mediterranean basin, where they overlap. Because of this biogeographic and ecological similarity, the environmental pattern of both taxa was found to be very significant. The physical–chemical analysis performed on the epicuticular waxes of C. siliquastrum and C. siliqua leaves provided relevant data that confirm the functional proximity between them. A striking resemblance was found in the epicuticular waxes of the abaxial surfaces of C. siliquastrum and C. siliqua leaves in terms of the dominant chemical compounds (1-triacontanol (C30) and 1-octacosanol (C28), respectively), morphology (intricate network of randomly organized nanometer-thick and micrometer-long plates), wettability (superhydrophobic character, with water contact angle values of 167.5 ± 0.5° and 162 ± 3°, respectively), and optical properties (in both species the light reflectance/absorptance of the abaxial surface is significantly higher/lower than that of the adaxial surface, but the overall trend in reflectance is qualitatively similar). These results enable us to include for the first time C. siliqua in the vicariant process exhibited by C. canadensis L., C. griffithii L., and C. siliquastrum.